Narrating Trauma through Metaphors and Technical Terms in Italian Patients’ Narratives (Comparatismi, 2022)
The urgent need to humanise the practice of medicine has led to the emergence of narrative medicine, where writing is a useful tool in patient-centred care. In the medical field, writing not only allows patients to reflect on their illness, but is also a way for doctors to create a closer relationship between themselves and their patients. Patients’ narratives have gained popularity in recent years due to globalisation and social media. Consequently, the number of patients willing to share their illness experience on the net is continuously increasing. In these narratives, the use of metaphors plays a particularly important role, since these are used to narrate subjective experiences. Therefore, the aim of this paper is to analyse both metaphors and technical terms used by Italian patients with haematological diseases when writing about their illness experience.
Keywords: Narrative medicine; Patients’ narratives; Metaphor; Haematological diseases; Patient-centred care.